Breakdown characteristics of CO/sub 2/ and N/sub 2/ containing SF/sub 6/ at different gap spacings - Onal, E.; Kalenderli, O.; Mardikyan, K. (IEEE, 2003)
AC breakdown strengths of CO/sub 2/, N/sub 2/, SF/sub 6/ and the mixtures of CO/sub 2/+SF/sub 6/ and N/sub 2/+SF/sub 6/ containing 0.5% and 4% of SF/sub 6/ in a nonuniform field were experimentally studied. The relative gas pressure and the electrode gap spacing were varied within the range of 100-500 kPa and of 5-20 mm respectively. The experimental results have shown that the addition of SF/sub 6/ to CO/sub 2/ and N/sub 2/ causes a significant increase the AC breakdown voltage with respect to CO/sub 2/ and N/sub 2/.